Kesenjangan antara Kurikulum Formal dan Praktik Pembelajaran Aktual dalam Penjaminan Mutu Pendidikan: Kajian melalui Observasi Partisipatif - Ine Rahayu Purnamaningsih; Kristina Damayanti; Karmah (Journal of Education Technology Information Social Sciences and Health, 2026)
Educational quality is often assessed through administrative indicators that emphasize the completeness of instructional documents. However, this approach tends to privilege formal compliance over the actual dynamics of teaching and learning in the classroom. This study examines the gap between the formal curriculum and actual classroom practice, while also exploring the contribution of participant observation to educational quality assurance. Using a qualitative case study design, data were collected through participant observation, in-depth interviews, and document analysis. The findings show that quality evaluation systems remain largely oriented toward administrative compliance, resulting in representations of educational quality that do not fully capture the realities of classroom learning. In practice, teaching and learning processes are dynamic, adaptive, and context-dependent, yet these dimensions are insufficiently reflected in formal assessment mechanisms. The study also reveals differing perspectives on educational quality among school management, teachers, and students, indicating that quality cannot be adequately understood through administrative indicators alone. These findings highlight the importance of integrating participant observation into quality evaluation systems in order to produce a more authentic, contextual, and comprehensive assessment of classroom learning.